The systematic significance of floral morphology, nectaries, and nectar concentration in epiphytic cacti of tribes Hylocereeae and Rhipsalideae (Cactaceae) - Almeida, Odair J.G.; Cota-Sánchez, J. Hugo; Paoli, Adelita Aparecida Sartori [UNESP] (Elsevier, 2013)
A long-standing interest in cactus taxonomy has existed since the Linnaean generation, but an appreciation of the reproductive biology of cacti started early in the 1900s. Numerous studies indicate that plant reproductive traits provide valuable systematic information. Despite the extensive reproductive versatility and specializations in breeding systems coupled with the striking floral shapes, the reproductive biology of the Cactaceae has been investigated in approximately 10% of its species. Hence, the systematic value of architectural design and organization of internal floral parts has remained virtually unexplored in the family. This study represents the most extensive survey of flower and nectary morphology in the Cactaceae focusing on tribes Hylocereeae and Rhipsalideae (subfamily Cactoideae). Our objectives were (1) to conduct comparative morphological analyses of flowers and floral nectaries and (2) to compare nectar solute concentration in these two tribes consisting of holo- and semi-epiphytic species. Flower morphology, nectary types, and sugar concentration of nectar have strong taxonomic implications at the tribal, generic and specific levels. Foremost, three types of nectaries were found, namely chamber nectary (with the open and diffuse subtypes), furrow nectary (including the holder nectary subtype), and annular nectary. All Hylocereeae species possess chamber nectaries, in which the nectarial tissue has both trichomes and stomata. The Rhipsalideae are distinguished by two kinds of floral nectaries: furrow and annular, both nectary types with stomata only. The annular nectary type characterizes the genus Rhipsalis. Nectar concentration is another significant taxonomic indicator separating the Hylocereeae and Rhipsalideae and establishing trends linked to nectar sugar concentration and amount of nectar production in relation to flower size. There is an inverse relationship between flower size and amount of nectar production in the smaller Rhipsalideae flowers, in which nectar concentration is more than two-fold higher despite the smaller volume of nectar produced when compared to the large Hylocereeae flowers. Variability of nectary morphology and nectar concentration was also evaluated as potential synapomorphic characters in recent phylogenies of these tribes. In conclusion, our data provide strong evidence of the systematic value of floral nectaries and nectar sugar concentration in the Cactaceae, particularly at different taxonomic levels in the Hylocereeae and Rhipsalideae. © 2013 Perspectives in Plant Ecology, Evolution and Systematics.
Keywords: Annular nectary; Cactoideae; Chamber nectary; Furrow nectary; Stomata; Trichomes